Endoscopic Thyroidectomy for Differentiated Thyroid Cancer - Yi Yang; Xiaodong Gu; Xiaoxiao Wang; Jianbin Xiang; Zongyou Chen (The Scientific World Journal)
Endoscopic thyroidectomy is a relatively new approach in treating differentiated thyroid cancer. Since last decades, more and more endoscopic thyroidectomies have been performed. We review the indications and contraindications, methods, and postoperational complications of this surgical procedure. Lots of surgical approaches have been developed in endoscopic thyroidectomy for differentiated thyroid cancer. Compared to conventional thyroidectomy, scarless endoscopic thyroidectomy has a superior cosmetic result. And it also reduces the incidence of hypesthesia, paresthesia, or feelings of self-consciousness. However, the outcome depends, to a large extent, on the skill of the operator and the learning curve being relatively long. With the development of surgical equipments and skills, operation time and complications will be reduced. Indications of endoscopic thyroidectomy will be widened and it will be more and more performed.